(untitled) (Journal of Bangladesh Academy of Sciences, 2025)
The findings of this study highlight a significant gap in the current educational curriculum regarding agricultural relevance and practical skill development. Most respondents—comprising both students and educators—strongly preferred integrating agriculture-focused subjects, especially in rural settings where farming remains central to livelihoods. Participants believe early exposure to agricultural education and hands-on practical experience can empower students with real-world skills, reduce rural-urban migration, and support local economic growth. Additionally, an agriculture-based curriculum has the potential to address key challenges such as youth unemployme nt, food insecurity, and environmental degradation. Such a curriculum could promote long-term ecological balance and economic resilience by fostering awareness and competence in sustainable agricultural practices. Therefore, incorporating agriculture into mainstream education is not merely an academic enhancement but a strategic move toward sustainable national economic development. J. Bangladesh Acad. Sci. 49(1); 113-121: June 2025